12 Exploring experiences of compassion, resilience and self-care in clinical psychologists working in palliative care. Issue 3 (1st September 2017) - Cramond, Laura; Fletcher, Ian; Rehan, Claire
Abstract : Introduction: Compassion fatigue refers to the emotional and physical exhaustion that can be felt by professionals in caring roles, whereas compassion satisfaction encompasses the positive aspects of helping others. Levels of compassion satisfaction and fatigue have been found to be inconsistent in palliative care professionals. This could have serious implications for patients, professionals, and organisations. Aim: This study explored the experiences of 12 clinical psychologists working in palliative care to learn more about the impact that supporting people at the end of life has on compassion and the support that professionals may require to remain resilient and practice self-care. Method: A qualitative approach was taken, using semi-structured interviews and interpretative phenomenological analysis. Results: Six overarching themes were identified: Being Part of Something Special, The Therapeutic Relationship at The End of Life, Pressure to do More With Less, The Change in Self as a Result of Involvement, The Idea of the Consummate Professional, and Practicing What you Preach. The professionals' experiences were characterised by the relationship between them and patients at the end of life, the lasting impact of the work on professionals, and the effects of recent organisational change in healthcare. Conclusions: Professionals working in palliative care should be supported to reflect on their experiences of compassion fatigue and satisfaction, and encouraged to consider how to practice good self-care to protect their well-being, build resilience and ensure the quality of patient care.